Structural Data on the Periplasmic Aldehyde Oxidoreductase PaoABC from Escherichia coli: SAXS and Preliminary X-ray Crystallography Analysis - Otrelo-Cardoso, Ana Rita (2021)
This work was financially supported by Fundacao para a Ciencia e Tecnologia (FCT-MCTES) through project PTDC/BIA-PRO/118377/2010, grants SFRH/BD/85806/2012 (ARC), SFRH/BPD/64917/2009 (MC), DAAD-441.00 and Deutsche Forschungsgemeinschaft Grant Le1171/6-1 (to SL). The access to the EMBL facilities was supported by the EU FP7 infrastructure grants P-Cube (Project Number 227764) and BioStruct-X (Project Number 283570).